Comparative study between meshes of polyester with collagen and polytetrafluoroethylene in the repair of defects produced in abdominal wall of rats - Naufel,Andrea Mendes de Oliveira (2012)
PURPOSE: To study the intraperitoneal use of polyester with collagen and polytetrafluoroethylene meshes in the correction of total ventral wall defects in rats. METHODS: Thirty two rats were evaluated and divided randomly into four groups and underwent laparotomy and preparation of total defects of the abdominal wall. Next, the correction of the defect with the intraperitoneal placement of the chosen mesh was performed. The rats were submitted to euthanasia at 30 and 90 days after surgery. Were analyzed the macroscopic adhesions and microscopic aspects, and applied stress rupture test RESULTS: All animals showed intraperitoneal adhesions in varying degrees, with no statistical significance difference. There was no difference also between groups in the evaluation of stress rupture tests. On the microscopic aspect, the A30 group had less inflammatory reaction and less formation of granulomas and foreign body reaction that the B30 group, with significant difference. CONCLUSIONS: There was no difference in intraperitoneal adhesion and tensile rupture strength among groups. Group B30 presented granulomatous inflammatory reaction at the site of mesh attachment to the wall significantly higher than the A30.